Legal actions against public authorities and private entities for medical misadventures: rethinking the periods of limitation - Rosli, Muhammad Noor Firdaus; Jahn Kassim, Puteri Nemie (Lexis Nexis, 2019)
Initiating legal actions against public authorities and private entities for personal injuries suffered during medical misadventures needs to be done within a specified period of time or else the action will be time barred. The rationale for imposing periods of limitation on such actions is, among others, to prevent stale claims and to encourage potential claims to be brought without unreasonable delay. In Malaysia, the period of limitation against public authorities is three years whereas for private entities, is six years for Peninsular Malaysia and three years for Sabah and Sarawak. The discrepancies between these periods have caused dissatisfaction and confusion amongst relevant stakeholders. In addition, legislations governing these limitation periods do not have provisions addressing issues relating to latent injuries which are considered crucial for medical negligence cases as injuries are only discernible when clear symptoms arise and come to the knowledge of the victims. In many instances, by the time they have knowledge that the injuries are attributable to the negligent acts; their actions may have already been time-barred. Several jurisdictions such as United Kingdom and Canada have introduced legislative changes to cater for issues arising under latent injuries specifically for medical negligence cases. These changes can provide valuable lessons for Malaysia in reforming the same and this would eventually uphold justice and fairness for victims of medical misadventures.